2016
DOI: 10.20944/preprints201611.0059.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lightweight Design Solutions in the Automotive Field: Environmental Modelling Based on Fuel Reduction Value Applied to Diesel Turbocharged Vehicles

Abstract: A tailored model for the assessment of environmental benefits achievable by "light-weighting" in the automotive field is presented. The model is based on the Fuel Reduction Value (FRV) coefficient, which expresses the Fuel Consumption (FC) saving involved by a 100 kg mass reduction. The work is composed of two main sections: simulation and environmental modelling. Simulation modelling performs an in-depth calculation of weight-induced FC whose outcome is the FRV evaluated for a wide range of Diesel Turbocharge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…As can be seen in Table 1, seven synonyms for the term "criterion" and eight synonyms for the term "lightweight design" were used in both singular and plural form. Synonyms for the term "criterion*" Synonyms for the term "lightweight design*" "Parameter" (Delogu et al, 2018) "Lightweight construction" (Schleinkofer et al, 2018) "Indicator" (Choudry et al, 2018) "Lightweight development" (defined by the authors) "Factor" (Hottle et al, 2017) "Lightweight engineering" (Caldwell et al, 2013) "Basis" (Koffler and Rohde-Brandenburger, 2010) "Lightweight optimization" (Wang et al, 2017) "Measure" (Delogu et al, 2016) "Mass reduction" (Hottle et al, 2017) "Multi-objective" (Wang et al, 2017) "Mass saving" (Qin et al, 2016) "Multi-criteria" (Kaspar et al, 2018) "Weight reduction" (Viqaruddin and Reddy., 2017) "Weight saving" (defined by the authors)…”
Section: Criteria For Lightweight Designmentioning
confidence: 99%
“…As can be seen in Table 1, seven synonyms for the term "criterion" and eight synonyms for the term "lightweight design" were used in both singular and plural form. Synonyms for the term "criterion*" Synonyms for the term "lightweight design*" "Parameter" (Delogu et al, 2018) "Lightweight construction" (Schleinkofer et al, 2018) "Indicator" (Choudry et al, 2018) "Lightweight development" (defined by the authors) "Factor" (Hottle et al, 2017) "Lightweight engineering" (Caldwell et al, 2013) "Basis" (Koffler and Rohde-Brandenburger, 2010) "Lightweight optimization" (Wang et al, 2017) "Measure" (Delogu et al, 2016) "Mass reduction" (Hottle et al, 2017) "Multi-objective" (Wang et al, 2017) "Mass saving" (Qin et al, 2016) "Multi-criteria" (Kaspar et al, 2018) "Weight reduction" (Viqaruddin and Reddy., 2017) "Weight saving" (defined by the authors)…”
Section: Criteria For Lightweight Designmentioning
confidence: 99%
“…Results recorded over a vehicle life cycle of 200,000 km driving revealed that when typical steel parts were replaced with aluminium parts, the vehicle consumed 1,447 to 1,590 litres JEDT 17,1 less gasoline. A tailored model to assess the environmental benefits of light weighting on diesel-turbocharged vehicles was presented by Delogu et al (2016) and was based upon fuel reduction value (FRV). Their results (ibid) showed that the FRV was within the range of 0.115-0.143 and 0.142-0.388 L/100 km  100 kg for mass reduction only and powertrain adaptation purposes.…”
Section: Lightweight Materials and Their Applicationsmentioning
confidence: 99%
“…In most markets, results from standardized test procedures are applied to determine greenhouse gas emissions that are the foundation for regulations or taxes [160]. In Europe, the assessment of real drivingemissions (RDE) has been introduced in order to determine pollutants from ICE vehicles [161].…”
Section: Automotivementioning
confidence: 99%
“…Several research studies have been published on physics-based approaches to determine mass-induced effects on a vehicles' fuel consumption [65,157,158,161,[164][165][166]. One important factor is the evaluation of drivetrain efficiencies to derive the relation between energy intake and output.…”
Section: Automotivementioning
confidence: 99%
See 1 more Smart Citation